2020
DOI: 10.1103/physrevlett.125.117206
|View full text |Cite
|
Sign up to set email alerts
|

Signatures of a Spin- 12 Cooperative Paramagnet in the Diluted Triangular Lattice of Y2CuTiO6

Abstract: We present a combination of thermodynamic and dynamic experimental signatures of a disorder driven dynamic cooperative paramagnet in a 50% site diluted triangular lattice spin-1 2 system: Y 2 CuTiO 6. Magnetic ordering and spin freezing are absent down to 50 mK, far below the Curie-Weiss scale ð−θ CW Þ of ∼134 K. We observe scaling collapses of the magnetic field and temperature dependent magnetic heat capacity and magnetization data, respectively, in conformity with expectations from the random singlet physic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 67 publications
5
20
0
Order By: Relevance
“…[27], and the references therein; also see recent Refs. [40,41] not covered in this review). Even in α-RuCl 3 , which has been established to be magnetically ordered, the muon relaxation rate is appreciable (∼0.5 MHz in a single crystal [42] and ∼2 MHz/∼4 MHz in a polycrystalline sample [43]) though smaller compared to ALIO.…”
Section: A μSrmentioning
confidence: 99%
“…[27], and the references therein; also see recent Refs. [40,41] not covered in this review). Even in α-RuCl 3 , which has been established to be magnetically ordered, the muon relaxation rate is appreciable (∼0.5 MHz in a single crystal [42] and ∼2 MHz/∼4 MHz in a polycrystalline sample [43]) though smaller compared to ALIO.…”
Section: A μSrmentioning
confidence: 99%
“…A power-law fit of low-temperature magnetic susceptibility thus suggests the realization of a random-singlet state attributed to the presence of isolated magnetic moments in the host lattice [25,29]. The data collapse is a remarkable feature found also in other QSL candidates with quenched disorder such as the honeycomb-lattice H 3 LiIr 2 O 6 [26] and the triangular-lattice Y 2 CuTiO 6 [45]. The data collapse behavior in the low-temperature region suggests the presence of random-singlets in LCTO induced by a small amount of quenched disorder in the lattice as predicted theoretically [29].…”
Section: B Magnetic Susceptibilitymentioning
confidence: 64%
“…As shown in Fig. 2 (c), a data collapse of M T −0.15 as a function of µ 0 H/T is found in LCTO, which could be a sign of the presence of random-singlets [45]. Furthermore, theoretically, it has been suggested that in the absence of spinorbit interaction, low-temperature magnetic susceptibility data of two-dimensional random-singlet states show a power-law χ ∝ T −γ behavior with γ < 1 [24].…”
Section: B Magnetic Susceptibilitymentioning
confidence: 67%
See 1 more Smart Citation
“…By including this site disorder effect, theoretically, several scenarios have been proposed for YMGO, such as highly anisotropic nearest-neighbor interactions [12], the random singlet (RS) state [13,14], randomness-induced QSL state [15], the mimicry of a spin liquid [16,17], and randomness induced spin-liquid-like phase in J 1 -J 2 model [18]. Among them, RS state and randomness-induced QSL have also been applied to other quantum magnets with disorder [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]. Meanwhile, a most recent study on high quality YMGO single crystals reveals a residual κ 0 /T term and series of quantum spin state transitions at the zero temperature limit, which suggest the survival of itinerant excitations and quantum spin state transitions in YMGO [38].…”
Section: Introductionmentioning
confidence: 99%